Eileen Chang : Romancing Languages, Cultures and Genres - Louie, Kam (Book collections on Project MUSE., 2012)
Eileen Chang has just been "rediscovered" outside China. But to date, there has been no book written in any language apart from Chinese that analyses her work. As well as being the first such book, the essays collected in here are written by scholars who are all, like Chang, bilingual and bicultural. The approach taken by the contributors in this essay is also multi-disciplinary, with theories and methodologies taken from areas ranging across many areas such literary, gender, historical and film studies. The book therefore should appeal to readers who want to find out more about a China that is beyond political rhetoric, where ordinary human feelings take precedence over concerns about the 'rise of China' and its place in the global village.